A Study on The Hidden Exploitation of Labor Process: The Case of Chinese Female Take-Away Riders - Wei Li; Chenkai Niu (Syntax Corporation Indonesia, 2022)
While creating more employment opportunities for Chinese women, algorithm-centered platform technologies have further exposed Chinese female take-out riders to hidden surplus value and gender labor exploitation. By examining the labor process, labor reproduction, and surplus value production process, this paper reveals that women face value extraction outside of the childcare and family spheres; at the same time, the platform technology controlled by the logic of capital further intensifies the exploitation of women's living space and social reproduction spheres; in addition, this technology-driven labor group also breeds hidden gender violence and other current situations. This study realistically illustrates the urgent need for the platform economy to address the hidden exploitation in the field of labor reproduction.